The international data governance landscape - Bernier, Alexander; Molnár-Gábor, Fruzsina; Knoppers, Bartha Maria (Journal of law and the biosciences, 2022)
As the adoption of digital health accelerates health research increasingly relies on large quantities of biomedical data. Research institutions scattered across a large number of jurisdictions collaborate in producing and analyzing biomedical big data. National data protection legislation, for its part, grows increasingly complex and localized. To respond to heterogeneous legal requirements arising in numerous jurisdictions, decentralized health consortia must develop scalable organizational and 6 technological arrangements that enable data flows across jurisdictional boundaries. In this article, proposals are made to enable health sector organisations to align established biomedical ethics process and data analysis practices to shifting data protection norms through both public law co-regulation, private law tools, and design-oriented approaches.
Gesehen am 06.07.2022